Situational Analysis on Voluntary Counseling and Confidential Testing in HIV/AIDS Patients Referred to Behavioral Center in lmam Khomeini Hospital, Tehran, Iran - Mahbobeh Hajabdolbaghi; Maryam Ghafarzadeh; Zahra Bayat Jozani; Minoo Mohraz; Molood Farrokhi; Maryam Foroughi; Mona Mohammadi Firouzeh (Shahrekord University of Medical Sciences, 2018)
Background and aims: Behavioral counseling centers are the main health organizations which are responsible for providing treatment and care for the patients living with HIV (PLWH). HIVpositive patients receive services through a unique counseling process called voluntary counseling and confidential testing (VCCT). Although there are reports regarding VCCT evaluation from other countries, not such an evaluation was found in Iran until this study, to the best of our knowledge. The study was performed to fulfill this necessity. Methods: Using consecutive method sampling, 314 subjects were sampled from the patients referred to Behavioral Counseling Center of Imam Khomeini hospital, Tehran, Iran. A combination of process and output evaluation of VCCT was performed in the biggest Behavioral Counseling Center of Iran at Imam Khomeini hospital, Tehran, Iran. Data were analyzed using descriptive statistics (percentages and averages). Results: Participants' response rate was 95.54%. Two shortcomings were found in the counseling process. Cronbach alpha reliability coefficient for this scale was 0.899, which was a desirable reliability for the questionnaire. As the main finding of the study, 48.33% of patients were not using antiretroviral medications regularly. An average number of patients (2.88) had HIV related stigma and fear of disclosure. In a quantitative study before testing in the study, it has been found that HIV patients did not have adequate information about their disease. Conclusion: Defects in the consultation process for the patients with HIV infection in the hospital were concluded. The quantity of consulting services for patients was in low level; therefore it is essential to improve consulting services for health promotion of the HIV patients.